WIRELESS SECURITY ISSUES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Wireless home networks, for small organizations, as well as multi-user institutions and public networks need to be secured. This is a topical issue, especially since wireless protocols do not always provide good protection. The article aims to discuss the vulnerabilities and privacy security issues associated with wireless networks. The tools airmon-ng for monitoring, WireShark for snooping, aircrack-ng for dictionary pre-generation and also airodump-ng and aireplay-ng present in Kali Lunix were used. The results of attacks and penetration tests performed on an experimental wireless connection protected with WPA2 show the vulnerability of wireless networks protected with this protocol. Therefore, accelerated implementation of WPA3 protocol is imperative.